2007
DOI: 10.1088/0957-4484/18/42/424009
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and transistor properties of phenyl-substituted tetrathiafulvalene derivatives

Abstract: The crystal structures, thin-film properties, and field-effect transistor (FET) characteristics of tetrathiafulvalene (TTF) derivatives with two phenyl groups are systematically investigated. The highest mobility, 0.11 cm(2) V(-1) s(-1), is observed in biphenyl-substituted TTF (1). The correlation between the crystal structures and the FET properties demonstrates that good transistor properties are associated with two-dimensional intermolecular interaction, which is achieved when the molecules are standing nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 53 publications
2
34
0
1
Order By: Relevance
“…Hole mobility in the range 0.1-1 cm 2 /Vs has been reported for solution-processed single crystals of DB-TTF, [18,19] whereas devices comprising vacuum-deposited DB-TTF thin films show field-effect mobility that ranges from 10 -2 to 10 -1 cm 2 /Vs ( Figure S1). [20][21][22][23] However, typically the devices are reported to exhibit large threshold voltages (V TH > 20 V) and are very unstable in environmental conditions…”
Section: Resultsmentioning
confidence: 99%
“…Hole mobility in the range 0.1-1 cm 2 /Vs has been reported for solution-processed single crystals of DB-TTF, [18,19] whereas devices comprising vacuum-deposited DB-TTF thin films show field-effect mobility that ranges from 10 -2 to 10 -1 cm 2 /Vs ( Figure S1). [20][21][22][23] However, typically the devices are reported to exhibit large threshold voltages (V TH > 20 V) and are very unstable in environmental conditions…”
Section: Resultsmentioning
confidence: 99%
“…37 (TTF)(TCNQ) has also been demonstrated to be an efficient electrode for n-channel transport. It was shown that in the very good electron donor TTF, the usual gold electrodes result in normally on states, while the smaller work-function organic (TTF)(TCNQ) metal leads to a lower off current and threshold voltage.…”
Section: Evaporated Ct Saltsmentioning
confidence: 99%
“…However, the following studies on thin-film devices based on 4 by Mori et al and by our group showed very poor FET performance, such as the low mobility, small on/off ratio, large off-current, and the lack of saturation current [28,29]. The reason might be attributed to the different measurement conditions.…”
Section: © 2008 Iupac Pure and Applied Chemistry 80 2405-2423mentioning
confidence: 78%
“…The reason might be attributed to the different measurement conditions. The poor FET performance was also found in the thin-film devices based on compounds 11-16 [29][30][31]. Similar to 4, these compounds have high HOMO levels, their thin films are labile to oxygen, and the resulting dopants increase the conductivity of the film in the off-or ungated-state and lead to aforementioned poor FET performance.…”
Section: © 2008 Iupac Pure and Applied Chemistry 80 2405-2423mentioning
confidence: 93%
See 1 more Smart Citation